2012
DOI: 10.1136/amiajnl-2011-000655
|View full text |Cite
|
Sign up to set email alerts
|

Incorporating molecular and functional context into the analysis and prioritization of human variants associated with cancer

Abstract: By aggregating mutations with known disease association at the domain level, the method was able to discover domain positions enriched with multiple occurrences of deleterious mutations while incorporating relevant functional annotations. The method can be incorporated into translational bioinformatics tools to characterize rare and novel variants within large-scale sequencing studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 55 publications
2
31
0
Order By: Relevance
“…We demonstrated that significant DS-Scores indicate that a mutation at a specific position is highly likely to be a contributor to disease in any protein containing the domain in which the mutations are located. In particular, we have shown that Mendelian disease mutations form clusters at protein domain sites [18]. In addition, results from Yue et al [19], Nehrt et al [20], and Peterson et al [18] have further shown that inherited and somatic cancer mutations cluster at specific sites at the protein domain level.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We demonstrated that significant DS-Scores indicate that a mutation at a specific position is highly likely to be a contributor to disease in any protein containing the domain in which the mutations are located. In particular, we have shown that Mendelian disease mutations form clusters at protein domain sites [18]. In addition, results from Yue et al [19], Nehrt et al [20], and Peterson et al [18] have further shown that inherited and somatic cancer mutations cluster at specific sites at the protein domain level.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, we have developed a statistical approach, the domain significance score (or DS-Score), for finding significantly mutated positions for individual protein domains [18]. We demonstrated that significant DS-Scores indicate that a mutation at a specific position is highly likely to be a contributor to disease in any protein containing the domain in which the mutations are located.…”
Section: Introductionmentioning
confidence: 99%
“…For example, some of the most frequent oncogenic mutations in human cancer affect analogous residues of the activation segment of the kinase domain and cause constitutive activation of several oncogenes, including FLT3 D835 mutations in acute myeloid leukemia, KIT D816 mutations in gastrointestinal stromal tumors, and BRAF V600 mutations in melanoma (Dibb et al, 2004; Greenman et al, 2007). Proteome-wide bioinformatics analysis of mutations in domains have been performed to identify domains enriched for alterations (Nehrt et al, 2012; Peterson et al, 2012; Yang et al, 2015) as well as to detect significantly mutated domain hotspots using multiple sequence analysis (Peterson et al, 2010; Yue et al, 2010). We here extend upon these analyses by performing a systematic pan-cancer analysis of recurrence of mutations in protein domains (hotspots and enrichment of mutations across the domain body) and identify dozes of unreported cancer-associated mutations that are not detection using standard gene-based approaches.…”
Section: Introductionmentioning
confidence: 99%
“…Proteome-wide analyses have been performed to identify domains enriched in missense mutations [45,47] [50] and to identify domain-centric positions of hotspot missense mutations [48,49] [50]. These studies focused exclusively on missense mutation and as yet, little attempt was to use these data to distinguish between activating and loss of function mutations in the majority of cases.…”
Section: Domain-based Approaches At Identifying Mutational Hotspotsmentioning
confidence: 99%